Intra-Operative Experience using Magnetic Resonance Imaging (MRI) Based Patient Specific Cutting Guides during Total Knee Arthroplasty - Albrecht, Ryan K.; Chong, Alexander C.M.; Wooley, Paul H.; Bhargava, Tarun (Kansas Journal of Medicine, 2016)
Background. The incidence of malalignment in total knee arthroplasty(TKA) using conventional instrument has beenreported as high as 25%. A relatively new TKA system involvesthe use of a preoperative magnetic resonance image(MRI) to obtain accurate implant placement more consistently.For broad acceptance of this new technique, it iscrucial to analyze the initial intra-operative experience. Thespecific aim of this study was to evaluate the initial intra-operativeexperience of a single surgeon using this new technique.Methods. A total of 15 knees (12 patients: 6 female and 6male) were reviewed from TKA procedures using the selectedmanufacturer’s patient specific cutting guides between January2011 and April 2013 at a single institution. Patient demographicand specific parameters and intra-operative alterationsof component positioning were recorded and evaluated.Results. The preoperative plan was able to predict correctly thesize of the implanted femoral component in 87% (n = 13) andtibial component in 80% (n = 12) of the cases. However, 60% (n= 9) of cases required additional intra-operative corrections onfemoral resection, and 73% (n = 11) required an additional 2 - 4mm correction on the tibial proximal resection. Twenty percent(n = 3) required additional tibial varus/valgus correction, butthere were no tibial slope corrections for any of the 15 cases.Conclusions. The initial intra-operative experience of a singlesurgeon using current patient specific cutting guides for a selectedmanufacturer to align femoral and tibial components duringTKA has raised some concerns. We agreed with previous studiesthat caution should be taken when using patient specific cuttingguides without supportive data. The findings of this study providedadditional evidence to contest the accuracy of patient specificcutting guides with respect to the initial experience of an orthopaedicsurgeon who is trained in total joint replacement. Theresults provided more evidence to assist orthopaedic surgeonsin the decision of whether to use these patient specific systemsversus conventional TKA methods. KS J Med 2016;9(2):22-26.